PEDAGOGICAL METHODS OF DEVELOPING LEGAL CULTURE IN STUDENTS (Web of Teachers: Inderscience Research, 2024)
Legal education is a pedagogical process aimed at the formation of skills and competencies in the organization of legal activity on the basis of theoretical and legal knowledge acquired by the person, the determination of positive legal qualities and the formation of legal culture. Legal education and upbringing are interrelated and dialectical in nature, and are a guarantee of the formation of a person's legal culture. Legal education plays a special role in the organization of civic education among students. The article discusses the methods of developing legal culture among students of higher education institutions.